Development of TUACA Flashcard Media (Learning to Read) to Improve the Reading Skills of Grade 1 Elementary School Students - Debi Ariska Saputri; Agustina Tyas Asri Hardini (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The reading ability of class I students at SDN 2 Candisari is still low. Observation results stated that 60% of students still classified as having below average reading skills and lack of use of learning media. The research objective was to develop TUACA flashcard media and test its validation level to improve students' reading skills in grade I. This research used the RD method and the ADDIE development model. The instruments included material and media validation questionnaires, validation of teacher responses, and an initial grade I reading ability test by applying qualitative descriptive analysis techniques in the form of percentages according to eligibility categories. Material validation results obtained a percentage of 75% (high category) and 95.83% (very high category) for media validation. The results of the validation of the class I teacher's response obtained a percentage of 97.32% (very high category). The average result of the analysis of the initial reading ability test before the TUACA flashcard media was applied obtained a percentage of 55% (enough category) and after the application of the media increased to 85% (very high category). Thus the TUACA flashcard media is feasible and can be used to improve the reading skills of grade I SD students.